Sleep as a biomarker for depression - Wichniak, Adam; Wierzbicka, Aleksandra; Jernajczyk, Wojciech (International review of psychiatry (Abingdon, England), 2013)
Abstract Sleep is a complex biological process that involves cyclic changes of brain activity. The smooth transition between wakefulness and sleep and cyclic succession of sleep stages depend on the function of numerous neurotransmitters that reciprocally influence each other. For this reason sleep is a very sensitive biomarker of brain functioning. This article provides an overview of sleep changes in depression, mechanisms involved in sleep regulation and pathophysiology underlying depression, studies on sleep as a biomarker for depression, effects of antidepressants on sleep EEG, and studies in depression with the use of quantitative sleep EEG analysis. Research on sleep in depression has provided several valuable biomarkers that are related to increased risk for depression, show worsening during depressive episode, and are related to treatment outcome and relapse risk during remission phase. Among many sleep parameters, increased REM density and diminished delta sleep ratio deserve special interest. Sleep studies are also an important research tool for antidepressant drug development. However, due to sensitivity of sleep parameters to pharmacological interventions, the patients have to be investigated before the start of pharmacological treatment or after washout from the antidepressant drug, to obtain reliable data on disease-related biological processes from polysomnography.